2013
DOI: 10.2105/ajph.2012.301052
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Discrimination and Their Impact on the Mental Health Among African American, Asian and Pacific Islander, and Latino Men Who Have Sex With Men

Abstract: Objectives We examined the associations between specific types and sources of discrimination and mental health outcomes among U.S. racial/ethnic minority men who have sex with men (MSM) and how these associations vary by race/ethnicity. Methods A chain-referral sample of 403 African American, 393 Asian and Pacific Islander (API), and 400 Latino MSM recruited in Los Angeles County, CA completed a standardized questionnaire. Results Past-year experiences of racism within the general community and perceived h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 32 publications
4
103
0
9
Order By: Relevance
“…Racial discrimination and other forms of discrimination that are perceived as stressful are associated with depression and anxiety. 156,168,169 Racism, discrimination, and oppression 170 in turn are associated with elevated blood pressure and markers of inflammation. In addition, a significant interaction between life-course SEP and racial discrimination in depressive symptoms has been reported.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…Racial discrimination and other forms of discrimination that are perceived as stressful are associated with depression and anxiety. 156,168,169 Racism, discrimination, and oppression 170 in turn are associated with elevated blood pressure and markers of inflammation. In addition, a significant interaction between life-course SEP and racial discrimination in depressive symptoms has been reported.…”
Section: Psychological Mechanismsmentioning
confidence: 99%
“…Ethnic minority MSM have unique life experiences and experiences of stigma and exclusion due to multiple social identities that elicit discriminatory reactions from within the general community, their racial/ethnic community and the mainstream gay community, which engender depressive mood (Balsam, Molina, Beadnell, Simoni and Walters, 2011; Choi, Paul, Ayala, Boylan, & Gregorich, 2013). A three-city study with a probability sample of 912 Hispanic MSM men revealed that 80% reported depressed mood and 17% reported suicidal ideation in the past 6 months, and that experiences of racial and sexual orientation discrimination predicted psychological symptoms and suicidal ideation (Diaz, Ayala, Bein, Henne, & Martin, 2001).…”
Section: Risk Of Hiv and Depression Among Hispanic Msmmentioning
confidence: 99%
“…For example, studies have shown that non-black MSM (BMSM) consistently rank black as the least preferred race of sex partner. 4 This dispreference is likely explained by a combination of racist attitudes [6][7][8] and the perception that BMSM are at greater risk for HIV acquisition. 4 These racial dispreferences result in increased insularity within BMSM sexual networks 9 and are hypothesized to influence the spread of HIV, in that numerous studies have demonstrated that HIV infection is more prevalent among MSM who are black, older, and of lower SES.…”
Section: Introductionmentioning
confidence: 99%